2022
DOI: 10.3390/ijms232112796
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Molecular Determinants in iRhoms1 and 2 That Contribute to the Substrate Selectivity of Stimulated ADAM17

Abstract: The metalloprotease ADAM17 is a key regulator of the TNFα, IL-6R and EGFR signaling pathways. The maturation and function of ADAM17 is controlled by the seven-membrane-spanning proteins iRhoms1 and 2. The functional properties of the ADAM17/iRhom1 and ADAM17/iRhom2 complexes differ, in that stimulated shedding of most ADAM17 substrates tested to date can be supported by iRhom2, whereas iRhom1 can only support stimulated shedding of very few ADAM17 substrates, such as TGFα. The first transmembrane domain (TMD1)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 58 publications
0
7
0
Order By: Relevance
“… 82 ADAM10 and ADAM17 are part of distinct multiprotein/substrate complexes. 82 , 83 In addition, previous studies demonstrated that proteases can modulate the activity of other proteases through prodomain cleavage. 84 Therefore, it is also possible that aberrant complex formation in FGFR2 ‐mutant ECs leads to the direct interaction of ADAM17 with ADAM10 and the subsequent modification of its proteolytic activity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 82 ADAM10 and ADAM17 are part of distinct multiprotein/substrate complexes. 82 , 83 In addition, previous studies demonstrated that proteases can modulate the activity of other proteases through prodomain cleavage. 84 Therefore, it is also possible that aberrant complex formation in FGFR2 ‐mutant ECs leads to the direct interaction of ADAM17 with ADAM10 and the subsequent modification of its proteolytic activity.…”
Section: Discussionmentioning
confidence: 99%
“…Although the molecular mechanisms of this crosstalk are not known, it is possible that the aberrant activation of ADAM17/EGFR‐mediated downstream signalling pathways in FGFR2 ‐mutant ECs leads to an increased proteolytic activity of ADAM10 or alternatively increased accessibility to its substrate 82 . ADAM10 and ADAM17 are part of distinct multiprotein/substrate complexes 82,83 . In addition, previous studies demonstrated that proteases can modulate the activity of other proteases through prodomain cleavage 84 .…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, we did not observe changes in the levels of soluble TYRO3, AXL, MERTK or TIM-3, suggesting that B. anthracis PGN induces selective substrate cleavage and/or alternative regulation beyond cell-surface expression. Work by Maretzky et al have shown that ADAM17 can cleave different substrates when in the presence of rhomboid proteins 1 or 2 (iRhom1, iRhom2), demonstrating that when complexed together, iRhom proteins can modify ADAM17 substrate specificity 62, 63 . To the best of our knowledge substrate specificity as a mechanism of receptor regulation has yet to be shown for the TYRO, AXL, MERTK (TAM) family.…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, mEFs lacking iRhom1 showed reduced shedding of TGFα [27]. Recently, it has been proposed that this iRhom‐mediated substrate selectivity of ADAM17 could be explained partly by the differential presentation by iRhom1 and iRhom2 of substrate cleavage sites to active ADAM17 [101]. Notably, ADAM17 substrate selectivity may also be regulated via certain signaling pathways in response to ADAM17 activity inducers, and irrespective of enhanced ADAM17 protease activity.…”
Section: Adam17 Substrate Selectivitymentioning
confidence: 99%